La solidarietà allo specchio. Il contributo delle neuroscienze e le ragioni del diritto - Pizzolato, Filippo; Comazzetto, Giovanni (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
Solidarity is exposed to the risk of objectification, according to an approach that is focused on the structure of our brain. In positivism the term ‘solidarity’ served to mirror the social interdependence; whereas now it refers to a ‘neuronal spasm’. In both cases, the anthropological consistency of solidarity remains in question. In contrast, solidarity according to case law in the Italian Constitutional Court, is conceptualised both as an obligation and as a spontaneous expression of the sociality that characterises the human nature. This article aims to summarise the main breakthroughs in neuroscientific research and analyse their impact on the way we conceptualise solidarity. The analysis will firstly focus on the discovery of mirror neurons by a group of researchers from the University of Parma. Secondly, it will consider not only what neurosciences say about solidarity, but also what they can’t say. Finally, it will suggest that we can’t explain solidarity only in neuroscientific terms.